ANALISIS EFISIENSI, EFEKTIVITAS DAN KONTRIBUSI PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) TERHADAP PENDAPATAN ASLI DAERAH (PAD) KABUPATEN BANJARNEGARA - Ghonimah Zumroatun Ainiyah; Yogka Arief Pratama; Enjang Pradikha (Jurnal Riset Keuangan dan Akuntansi, 2021)
The problems in this study are (1) Local Own Revenue (PAD) after the transfer by the management of the Land and Building Tax on Rural and Urban (PBB-P2) to a rapidly increasing Local Tax. (2) Local Own Revenue (PAD) within 5 (five) years always increases both before and after the transfer of the Rural and Urban Land and Building Tax (PBB-P2) to Regional Tax. This study aims to determine the level of efficiency, effectiveness, and contusion of PBB-P2 to PAD Banjarnegara Regency.This type of research is quantitative with descriptive studies or called quantitative descriptive. The data used in this study are primary and secondary data. The subject of this research is the Regional Revenue, Financial Management and Asset Agency (BPPKAD) of Banjarnegara Regency. While the object of this research is the Rural and Urban Land and Building Tax (PBB-P2). Data analysis in this research uses interpretation scale.The results of this study indicate that the level of efficiency of PBB-P2 acceptance of Banjarnegara Regency in 2014-2018 as a whole shows the criterion value of interpretation is very efficient, with an average of 2%. The level of effectiveness of PBB-P2 acceptance of Banjarnegara Regency in 2014-2018 as a whole shows the criteria of interpretation values are very effective, with an average of 108%. The contribution of PBB-P2 receipts to the PAD of Banjarnegara Regency in 2014-2018 shows that the criteria for interpretation are very poor, with an average of 9%. Keywords: Efficiency, Effectiveness, Contributions, Rural and Urban Land and Building Tax (PBB-P2), Local Revenue (PAD).